Right thoughts, right words, right actions?: The EU‘s application of the Cyber Diplomacy Toolbox [data] - Sachs, Annika; Schmalfeldt, Imke; Zettl-Schabath, Kerstin (Universität, 2024)
This dataset is the first to address the application of the EU's cyber diplomacy toolbox (CDT) by EU institutions/actors since 2017 until the end of May 2023. Based on this, the related research paper highlights trends, patterns, and anomalies in previous usage that can be identified and analysed in the respective political context. The publication is complemented by insights from the European Repository of Cyber Incidents (EuRepoC) to evaluate the intended impact of the measures in a more detailed manner.